Product Information and Purchasers Cognitive Response: A Case of Thai Vernacular Artefacts Design - Sarath Simsiri; Napadon Sahachaisaeree (My University, 2012)
Traditionally and locally made handicrafts such as Thai silk, pottery and wood carving are considered part of products with vernacular style. Development of such products need careful considerations, consumer needs and perceptions are among crucial factors determining the success of the design, and therefore, determining the acceptance of the products. Distinctive consumers–tourists from oversea, local folks, and urbanites–possess different tastes and perceptions. Product development as such thus has conflicting directions and implications, which need guideline with empirical basis.
Keywords: Handicraft; Consumer Packaging Perceptions and Trends